Impedance Matching Method for 6.78 MHz Class-E2-Based WPT System - Yi Zhang; Yue Feng; Sheng Liu; Jiande Wu; Xiangning He (Energies, 2021)
The performance of a conventional Class-E2-based WPT system is sensitive to system parameters such as the coil coupling coefficient and load variation. System efficiency decreases rapidly when the coil coupling coefficient and load deviate from their optimum values. In this paper, an impedance matching method and a design procedure are proposed to maintain high system efficiency over a wider range of coupling coefficient and load variations. The load-pull technique is adopted to identify the high-efficiency load region of a Class-E power amplifier (PA), and a double-L-type impedance matching network (IMN) is proposed to transform the load impedance of a Class-E PA into a high-efficiency working region. Compared to a single L-type IMN, a double-L-type IMN is more flexible and has better tuning performance. A 6.78 MHz Class-E2-based WPT system was built to validate the proposed design method. The experimental results show that the proposed double-L-type IMN can significantly attenuate the decline in Class-E PA efficiency when system parameters dynamically change. With a double-L-type IMN, the WPT system could maintain high efficiency (over 55%) under a wider range of coil coupling coefficient and load variations. The peak system efficiency reached 83.2% with 13.7 W output power. The impedance matching method and design procedure in this paper could provide a practical solution for building a high-efficiency WPT system with strong robustness.